Pengelompokan Faktor-Faktor Pengaruh Online Repurchase Intention Pada Pengguna Aplikasi Webstore Pencari Kost Online - Muhammad Iqbal; Siti Nurjanah; Haryanto; Moh Slamet Sutrimo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
T his study aims to categorize online boarding search App/Webstore users based on factors that influence their online repurchase intention. The eight factors analyzed include perceived value, perceived ease of use, perceived usefulness, firm's reputation, privacy, trust, reliability, and functionality. Data obtained from 160 respondents who use the application/webstore kost finder. The analysis method used is K-Means clustering. The results show the formation of 2 clusters, namely cluster 1 of 100 respondents with high factor influence and cluster 2 of 60 respondents with low factor influence. The difference in the average score on each factor between the two clusters indicates that cluster 1 is more satisfied and trusting of the service than cluster 2. These results can be a reference for companies in improving service quality and marketing strategies.